Applying the ARIAS Learning Model with QuizWhizzer Support to Enhance Students’ Understanding of Mathematical Concepts - Ergayanti, Della Santika; Najibufahmi, Muhamad (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Students’ low level of mathematical conceptual understanding requires more effective learning strategies. Research integrating the ARIAS learning model with interactive digital media such as QuizWhizzer is still limited. This study examined the effects of the ARIAS learning model assisted by QuizWhizzer, the ARIAS model alone, and Conventional learning on high school students’ mathematical conceptual understanding. A quantitative approach with a post-test only control group design was employed, involving three Grade XI classes at SMA Muhammadiyah 1 Pekajangan. The instrument was an essay test developed from indicators of mathematical conceptual understanding, and data were analyzed using Scheffe’s post hoc test. The findings showed that both the ARIAS model and the ARIAS model assisted by QuizWhizzer significantly improved students’ conceptual understanding compared to Conventional learning. However, no significant difference was found between the ARIAS model with and without QuizWhizzer. These results indicate that QuizWhizzer did not substantially enhance the effectiveness of the ARIAS model. The study highlights the importance of further investigation into the integration of digital media within specific learning models to maximize their potential impact on mathematics learning.